EXCHANGE RATE ECONOMICS AND MACROECONOMIC FUNDAMENTALS - Argamaya, Argamaya (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
Financial crises have a long history. Recently, several international crises emerged: the Mexican and Argentina currency and debt crisis of 1973-1982 and 1978-1981 respectively, the exchange rate crises following the abandonment of the European Exchange Rate Mechanism in 1992, the Tequila Effect resulting from the Mexican peso devaluation in 1992, the Asian Flu of 1997 resulting after Thailands devaluation and the Russian Cold which arose from the collapse of the rubble in 1998. These episodes of international financial turmoil attracted worldwide attention; causes, impact and policy implications have been studied extensively.